CHARTING THE EVOLUTION AND FUTURE TRAJECTORY OF FLIPPED CLASSROOM MODELS: A BIBLIOMETRIC JOURNEY THROUGH A DECADE OF RESEARCH ON SCOPUS (2013-2023) - Stang, Taufik Hidayat; Rifai, Alfan; Maksum, Muh. Nur Rochim (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
To ascertain the trajectory and growth of flipped classroom research in Scopus-indexed articles on flipped classroom from 2013 to 2023, this study used bibliometric analysis. Rstudio and Microsoft Excel were then used to examine the collected data. The simultaneous incidence of keywords and document citations can be shown using VOSviewer. 3,558 publications that met the given function, topic, and criteria were discovered by the author. Based on the research, the yearly rate is 5.12%, and in 2021, there will be the highest number of publications on flipped classrooms. The nation that contributes the greatest number of articles to the Chinese Academy of Sciences is China. The most prolific writer on the subject of flipped classrooms is Salvati, L. The scope of the bibliometric analysis was restricted to data from Scopus. This study does not incorporate databases from other countries or countries. This study offers suggestions for more research in addition to a concise summary of the literature that is currently available to scholars working in this field